2009
DOI: 10.1124/jpet.108.149435
|View full text |Cite
|
Sign up to set email alerts
|

Proton Acts as a Neurotransmitter for Nicotine-Induced Adrenergic and Calcitonin Gene-Related Peptide-Containing Nerve-Mediated Vasodilation in the Rat Mesenteric Artery

Abstract: Nicotine stimulates presynaptic nicotinic acetylcholine receptors in perivascular adrenergic nerves and releases unknown transmitter(s) that activate transient receptor potential vanilloid-1 (TRPV1) located on calcitonin gene-related peptide (CGRP)-containing (CGRPergic) nerves, resulting in vasodilation. The present study investigated a potential transmitter transmitting between perivascular adrenergic nerves and CGRPergic nerves. Rat mesenteric vascular beds without endothelium were contracted by perfusion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 17 publications
2
38
0
Order By: Relevance
“…9), suggesting that sympathetic adrenergic nerves innervate the male mouse mesenteric perivascular nerves, like in male rat mesen- teric arteries. These findings obtained from male mouse mesenteric vascular beds are in good accordance with previous reports in male rat mesenteric vascular beds (4, 13,15,21). It is also likely that TH-immunopositive nerves innervating the small arteries are responsible for the neurogenic vasoconstrictor response.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…9), suggesting that sympathetic adrenergic nerves innervate the male mouse mesenteric perivascular nerves, like in male rat mesen- teric arteries. These findings obtained from male mouse mesenteric vascular beds are in good accordance with previous reports in male rat mesenteric vascular beds (4, 13,15,21). It is also likely that TH-immunopositive nerves innervating the small arteries are responsible for the neurogenic vasoconstrictor response.…”
Section: Discussionsupporting
confidence: 82%
“…It appears that the PNS-induced vasoconstrictor response is neurogenic in nature. Furthermore, the adrenergic neuron blocker guanethidine, which blunts the neurogenic release of the adrenergic neurotransmitter norepinephrine (13), abolished the PNS-induced vasoconstrictor response, suggesting that the sympathetic adrenergic nerve mediates the neurogenic vasoconstriction. Furthermore, the present immunohistochemical study demonstrated male mouse mesenteric arteries and veins to be densely innervated by adrenergic TH-immunopositive nerve fibers, which were sensitive to the adrenergic toxin 6-OHDA, but not capsaicin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…10,12) After being anesthetized with sodium pentobarbital (50 mg/kg, intraperitoneally (i.p. )), each rat was fixed on its back, and a middle incision was gently made in the abdomen, exposing the jejunum and superior mesenteric artery.…”
Section: Methodsmentioning
confidence: 99%
“…Nitric oxide (NO), acetylcholine (ACh), and sodium nitroprusside (SNP) were selected as model vasodilators due to their well-known pharmacological characteristics. 6,7,9,10) In addition, they involve a common process to exert vasodilatory activity. NO acts as an endothelium-derived relaxing factor, 6,11) stimulating soluble guanylate cyclase to promote cGMP production from GTP.…”
mentioning
confidence: 99%
“…In rat perfused mesenteric vascular beds with active tone, PNS has been shown to produce an initial vasoconstriction followed by a long-lasting vasodilation (11). Since guanethidine abolished the PNS-induced vasoconstriction ( Fig.…”
mentioning
confidence: 99%